Afro-Catholic festivals in the Americas : performance, representation, and the making of Black Atlantic tradition - Fromont, Cécile (Africana religions., 2019)
"Explores how, in the Americas, people of African birth or descent found spiritual and social empowerment in the orbit of the Church. Draws connections between Afro-Catholic festivals and their precedents in the early modern Christian kingdom of Kongo"--Provided by publisher